Spatiotemporal relationships of threatened cetaceans and anthropogenic threats in the lower Yangtze system - Mogensen, Lisa M. W.; Mei, Zhigang; Hao, Yujiang; Hudson, Michael A.; Wang, Ding; Turvey, Samuel T. (Frontiers in Conservation Science, 2022)
The impacts of fisheries interactions on cetaceans can be challenging to determine, often requiring multiple complementary investigative approaches. The Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis), one of the few Critically Endangered cetaceans, is endemic to the middle-lower Yangtze drainage, a system impacted by multiple anthropogenic pressures. Bycatch mortality is implicated in regional porpoise decline, but the significance and dynamics of porpoise interactions with fishing activities and other threats remain poorly understood. We conducted boat-based surveys to map seasonal distributions and spatial congruence of porpoises and two potential threats (fishing and sand-mining), and an interview survey of fishing communities to understand temporal patterns and drivers of regional fishing activity, across Poyang Lake and the adjoining Yangtze mainstem. Variation in harmful and non-harmful gear use (non-fixed nets versus static pots and traps) between these landscapes might be an important factor affecting local porpoise status. Within Poyang Lake, spatial correlations between porpoises and threats were relatively weak, seasonal porpoise and threat hotspots were located in different regions, and two protected areas had higher porpoise encounter rates and densities than some unprotected sections. However, porpoise hotspots were mostly in unprotected areas, threats were widely observed across reserves, and more fishing and sand-mining was seasonally observed within reserves than within unprotected areas. Compared to null distributions, porpoises were detected significantly closer to fishing activities in summer and further from sand-mining in winter, indicating possible spatial risks of gear entanglement and disturbance. Reported porpoise bycatch deaths are associated with fixed and non-fixed nets, hook-based gears and electrofishing. Longitudinal patterns in reported gear use indicate that hook-based fishing has decreased substantially and is generally conducted by older fishers, and significantly fewer respondents now practice fishing as their sole source of income, but electrofishing has increased. This combined research approach indicates a continued potential risk to porpoises from changing fisheries interactions and other threats, highlighting the importance of fishing restrictions and appropriate support for fishing communities impacted by this legislation. A potential “win-win” for both biodiversity and local livelihoods could be achieved through wider use of static pots and traps, which are not associated with bycatch deaths.